Enhancement of mechanical properties of low stacking fault energy brass processed by cryorolling followed by short-annealing. (15th February 2015) - Kumar, Ravi; Dasharath, S.M.; Kang, P.C.; Koch, Carl C.; Mula, Suhrit
Highlights: Bulk-size ultrafine grained brass prepared by cryorolling of LFE commercial alloy. A good combination of YS and ductility attained by cryorolling followed by annealing. The LFE caused formation of subgrains and nanotwins to achieve the high YS & ductility. Fractography analysis corroborated mechanical behavior of the cryorolled and annealed samples. Abstract: The mechanical properties and microstructural characteristics of ultrafine grained low stacking faulty energy (SFE) brass processed by cryorolling were investigated in the present work. The commercial brass with 18 wt.% Zn was subjected to cryorolling to obtain specimens with different percentage of reduction in area (RA). Short time post-processing annealing was carried out for the specimens with maximum RA (90%) to enhance their ductility. The mechanical properties of all the specimens were assessed by tensile tests and hardness measurements. Microstructural analysis was carried out by optical microscopy, X-ray diffraction (XRD), atomic force microscopy (AFM) and electron microscopy (EM). The maximum yield strength (YS) of 600 MPa with 2.1% ductility was obtained for the cryorolled samples with 90% RA. The YS decreased to 452 MPa with a corresponding increase in the ductility (10%) after annealing at 225 °C. The YS of the cryorolled + annealed sample is found to be 465% higher compared to that of the as-received specimens (YS = 80 MPa). Fractography analysis of the 90% rolled specimens showed a brittle fracture; while, presence of dimples marks on the fractured surface of the annealed specimens indicated a ductile failure. The low SFE of the alloy plays a vital role on the deformation mechanisms during cryorolling and simultaneous improvement of the YS and ductility. Hence, improvement in the mechanical properties has been discussed in the light of refinement of microstructure, formation of sub-grains and nano-twins driven by the low SFE.